Immunogenicity profiling and distinct immune response in liver transplant recipients vaccinated with SARS-CoV-2 inactivated vaccines - Duan, Binwei; Zhang, Gongming; Wang, Wenjing; Yin, Jiming; Liu, Mengcheng; Zhang, Jing; Chen, Dexi; Ouyang, Yabo; Li, Guangming (Frontiers in Immunology, 2022)
SARS-CoV-2 vaccination has been recommended for liver transplant (LT) recipients. However, our understanding of inactivated vaccine stimulation of the immune system in regulating humoral and cellular immunity among LT recipients is inadequate. Forty-six LT recipients who received two-dose inactivated vaccines according to the national vaccination schedule were enrolled. The clinical characteristics, antibody responses, single-cell peripheral immune profiling, and plasma cytokine/chemokine/growth factor levels were recorded. Sixteen (34.78%) LT recipients with positive neutralizing antibody (nAb) were present in the Type 1 group. Fourteen and 16 LT recipients with undetected nAb were present in the Type 2 and Type 3 groups, respectively. Time from transplant and lymphocyte count were different among the three groups. The levels of anti-RBD and anti-S1S2 decreased with decreasing neutralizing inhibition rates. Compared to the Type 2 and Type 3 groups, the Type 1 group had an enhanced innate immune response. The proportions of B, DNT, and CD3+CD19+ cells were increased in the Type 1 group, whereas monocytes and CD4+ T cells were decreased. High CD19, high CD8+CD45RA+ cells, and low effector memory CD4+/naïve CD4+ cells of the T-cell populations were present in the Type 1 group. The Type 1 group had higher concentrations of plasma CXCL10, MIP-1 beta, and TNF-alpha. No severe adverse events were reported in all LT recipients. We identified the immune responses induced by inactivated vaccines among LT recipients and provided insights into the identification of immunotypes associated with the responders.